2022
DOI: 10.3390/jcm11123332
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Laparoscopy versus Robotic-Assisted Aortic Lymph-Nodal Staging for Locally Advanced Cervical Cancer: A Systematic Review and Meta-Analysis

Abstract: Aortic lymph node metastases are a relative common finding in locally advanced cervical cancer. Minimally invasive surgery is the preferred approach to perform para-aortic lymph nodal staging to reduce complications, hospital stay, and the time to primary treatment. This meta-analysis (CRD42022335095) aimed to compare the surgical outcomes of the two most advanced approaches for the aortic staging procedure: conventional laparoscopy (CL) versus robotic-assisted laparoscopy (RAL). The meta-analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The aim of this systematic review is to evaluate the diagnostic performance of AI technologies in cervical cancer and pre-cancerous lesions. Estimating the prognosis of cervical cancer is one of the most difficult tasks because its management requires a variety of cancer treatment approaches [ 162 , 163 ], which may even impair quality of life to a significant extent [ 164 , 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this systematic review is to evaluate the diagnostic performance of AI technologies in cervical cancer and pre-cancerous lesions. Estimating the prognosis of cervical cancer is one of the most difficult tasks because its management requires a variety of cancer treatment approaches [ 162 , 163 ], which may even impair quality of life to a significant extent [ 164 , 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery has gained popularity and significance in MIS over the last few years and clinicians hope to further expand on the recognized advantages of the laparoscopic surgical technique for patients [ 7 ]. In this context, many scientific papers have reported on patient outcomes and surgical data when applying robotic surgery which has been summarized in recent systematic reviews [ 8 , 9 ]. In addition, it is presumed that robotic surgery provides ergonomic benefits for surgeons by reducing physical demands [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found higher rate of recurrence in the full staged patients (9.5% vs. 4.8%), despite it was not statistically significant. Systematic lymphadenectomy is indeed associated with high morbidity, even when performed by skilled surgeons [21,22] and, for this reason, the choice to perform this procedure should be carefully balanced and based on the available evidence. In this scenario, recent and promising data suggested that sentinel-node biopsy in early-stage ovarian cancer is feasible and has the potential to provide reliable and useful information on nodal status, and may allow the avoidance of systematic lymphadenectomy in the majority of patients [23,24].…”
Section: Discussionmentioning
confidence: 99%